Smooth Operator : Remittances and Fiscal Shocks - Beaton, Kimberly (IMF Working Papers; Working Paper ;, 2017)
With 250 million migrants globally, remittances are one of the major sources of income in many developing countries. While there is abundant evidence that remittances facilitate consumption smoothing in receving countries, the literature has not considered whether this effect varies with the fiscal stance and during fiscal shocks. Therefore, we investigate the impact of remittances on the stability of household consumption, using both cross-country and household-level datasets. Our focus is on whether the consumption-smoothing effect changes with fiscal policy phases and whether remittances and government support are substitutes or complements in stabilizing household consumption. We find that remittances help smooth consumption, and hence improve welfare, more during fiscal consolidation episodes, while this impact is insignificant during fiscal expansions. The results also indicate that the effect is more pronounced in countries with greater reliance on remittances.